DAPATKAH STRATEGI KONTRARIAN DITERAPKAN DIPASAR MODAL INDONESIA? (Pengujian Anomali Winner-Loser di Bursa Efek Jakarta) - Titi Dewi Warninda; Marwan Asri Sw (Faculty of Economics and Business, Universitas Gadjah Mada, 1998)
The fluctuation of of stock prices, in many occassions, are related to so called market anomalies. One of those anomalies is known as a winnerloser anomaly. A winner-loser anomaly is identified when stocks that initially earned extremely positive abnormal returns (winners) or extremely negative abnormal returns (losers) experience extended reversal, so that losers can outperform winners. The presence of this anomaly creates a contrarian investment strategy: buy loserstocks and sellshort the winner-stocks, in order to earn significant positif abnormal return. De bondt and Thaler (1985) suggested the overreaction hypothesis as an explanation of this anomaly. The hypothesis claims that the market tends to overreact to (especially new and dramatic) information. The market overvalues stock prices as a reaction to good news and undervalues stock prices as a reaction to bad news. This phenomenon is reversed when it is recognized that the market has overreacted to the information. The purpose of this research is to test the existence of winnerloser anomaly in the Jakarta Stock Exchange. Using market adjusted abnormal return, data from December 1990 to June 1997, and overlapping six months formation/test periods, this research does not find any indication of market overreaction. So, it is not suggested that investor can use the contrarian investment strategy. This research also finds that there is no significant difference between average size of winners and losers.